2011
DOI: 10.1016/j.irle.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Medical malpractice and physician liability under a negligence rule

Abstract: A model of costly medical malpractice claims, based on Bayes Rule, is developed to examine the effects of physicians being liable for actual damage under a negligence rule. This model is consistent with empirical evidence concerning the pattern of claims. It is shown that compensating actual damage does not provide physicians with appropriate incentives to spend the second best optimal amount of time with patients or to treat the second best optimal number of patients. As a result, too much medical malpractice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Wright developed a model of costly medical malpractice claims to examine the effects of physicians being liable for actual damages under a negligence rule. He showed that compensating actual damage does not provide physicians with appropriate incentives to spend the second best optimal amount of time with patients or to treat the second best optimal number of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Wright developed a model of costly medical malpractice claims to examine the effects of physicians being liable for actual damages under a negligence rule. He showed that compensating actual damage does not provide physicians with appropriate incentives to spend the second best optimal amount of time with patients or to treat the second best optimal number of patients.…”
Section: Introductionmentioning
confidence: 99%